Assessing the multi-dimentional impact of lakefront development: a case of telibandha lake, Raipur(C.G.) - Rathore, Abhishek (SPA Bhopal, 2025)
Urban waterfronts have constantly fascinated cities worldwide, offering both economic potential and opportunities for transformation. In recent decades, waterfront development has emerged as a major strategy for urban revitalization, aiming to bring new life into underutilized waterfront areas and create vibrant, livable neighborhoods. Telibandha Talab, located in Raipur, launched a transformative waterfront development project in 2012, aiming for the conversion of its idle lake into a thriving center for recreation, culture, and commerce. This study seeks to explore the multidimensional impact of waterfront development, using Telibandha Lake as a case study. Adopting a comprehensive approach, this research explores the social, economic, and environmental implications of the Telibandha Lakefront development project. Through meticulous analysis, it identifies key parameters within these domains, based on comprehensive literature reviews and consultations with urban planning and environmental sustainability experts. Parameters were thoroughly examined to assess the impact of waterfront development on each aspect. Data collection involved a combination of secondary sources, including research papers and office visits, complemented by primary sources such as surveys, focus group discussions, and interviews with officials. Utilizing a scoring system, data was evaluated for both pre-development and post-development phases, allowing for a comparative analysis of impacts. Additionally, an Analytical Hierarchy Process (AHP) analysis was conducted to prioritize parameters, guiding the identification of key areas for improvement. The research concludes with the identification of challenges and the formulation of targeted recommendations to enhance the Telibandha Lakefront development. By systematically assessing the multifaceted impacts and prioritizing areas for intervention, this study offers valuable insights for authorities, urban planners, and stakeholders involved in waterfront revitalization projects. Through collaborative efforts and strategic interventions, the vision of a vibrant and sustainable waterfront can be realized, fostering economic growth, social well-being, and environmental resilience in Raipur and beyond.
Keywords: Urban Waterfront Development; Planning